O PURGATÓRIO DA DIVINA COMEDIA: uma analogia possível com a imigração italiana no ES - Angarita, Diana Mariluz Perez (2021)
This investigation aims to investigate the first years of Italian immigration in Espírito Santo, seeking to understand the sensitive relationship of these immigrants with space, nature, and climate and above all, with the culture of this new land that seems to put the Italian subject back into the classic figuration of the suffering environment of Dantesque Purgatory. In this way, we make the analogy between Dante Alighieri's Purgatory and Italian immigration to the state of Espírito Santo from the perspective of Virginia Tamanini novel Karina.